Understanding structure, function, and mutations in the mitochondrial ATP synthase - Ting Xu; Vijayakanth Pagadala; David M. Mueller (Microbial Cell)
The mitochondrial ATP synthase is a multimeric enzyme complex with an overall molecular weight of about 600,000 Da. The ATP synthase is a molecular motor composed of two separable parts: F1 and Fo. The F1 portion contains the catalytic sites for ATP synthesis and protrudes into the mitochondrial matrix. Fo forms a proton turbine that is embedded in the inner membrane and connected to the rotor of F1. The flux of protons flowing down a potential gradient powers the rotation of the rotor driving the synthesis of ATP. Thus, the flow of protons though Fo is coupled to the synthesis of ATP. This review will discuss the structure/function relationship in the ATP synthase as determined by biochemical, crystallographic, and genetic studies. An emphasis will be placed on linking the structure/function relationship with understanding how disease causing mutations or putative single nucleotide polymorphisms (SNPs) in genes encoding the subunits of the ATP synthase, will affect the function of the enzyme and the health of the individual. The review will start by summarizing the current understanding of the subunit composition of the enzyme and the role of the subunits followed by a discussion on known mutations and their effect on the activity of the ATP synthase. The review will conclude with a summary of mutations in genes encoding subunits of the ATP synthase that are known to be responsible for human disease, and a brief discussion on SNPs.